Transient vibration control using nonlinear convergence active vibration absorber for impulse excitation. (15th February 2019) - Wang, Xi; Yang, Bintang
Highlights: The active vibration absorber (ADVA) is mathematically imitated by a mass body and a voice coil motor. The ADVA is made up of equivalent dynamic modeling equations and frequency estimator. The nonlinear ADVA can shorten the convergence time of vibration suppressing. The nonlinear ADVA can achieve faster decrements for oscillation attenuation. Abstract: This paper presents a nonlinear convergence algorithm for active dynamic vibration absorber (ADVA) to control the transient vibration caused by the impulse excitation. The proposed nonlinear ADVA is made up of equivalent dynamic modeling equations and frequency estimator. The ADVA is mathematically imitated by a mass body and a voice coil motor (VCM). The VCM plays two roles in this study. On one hand, the algorithm-controlled Lorentz force of the VCM is actively utilized to suppress the transient response of primary system. On the other hand, the VCM also acts as a magnetic damper, which helps attenuate the transient vibration passively. The nonlinear convergence estimator is applied to simultaneously satisfy the requirements of fast convergence rate and small steady state frequency error, which are incompatible for the linear convergence estimator. The experiments demonstrate that the nonlinear ADVA can shorten 70% of the convergence time than the linear ADVA. The nonlinear ADVA and VCM magnetic damper work together and help eliminate 95% of the uncontrolled transient vibration at 1.5 s.